What matters most and for whom? A cross-sectional study exploring goals of health professionals in German neonatal intensive care units - Anne Mensen; Bernhard Roth; Ludwig Kuntz; Michael Wittland; Verena Glöckner; Felix Miedaner (BMJ Open, 2021)
Quality of care largely depends on successful teamwork, which in turn needs effective communication between health professionals. To communicate successfully in a team, health professionals need to strive for the same goals. However, it has been left largely unaddressed which goals professionals consider to be important. In this study, we aim to identify these goals and analyse whether differences between (1) personal and organisational goals, (2) different professions and (3) hierarchical levels exist in neonatal intensive care units (NICUs). Goals were identified based on a literature review and a workshop with health professionals and tested in a pilot study. Subsequently, in the main study, a cross-sectional employee survey was undertaken. 1489 nurses and 537 physicians from 66 German NICUs completed the questionnaire regarding personal and organisational goal importance between May and July 2013. Answers were given based on a 7-point Likert scale varying between none and exceptionally high importance. Results show that the goals can be subdivided into three main goal dimensions: patients, parents and staff. Furthermore, our results reveal significant differences between different professions and different hierarchical level: physicians rated patient goals with a mean (95%0.167emCI) importance of 6.37 (6.32 to 6.43), which is significantly higher than nurses with a mean (95%0.167emCI) importance of 6.15 (6.12 to 6.19) (p<0.01). Otherwise, nurses classified parental goals as more important (p<0.01). Furthermore, professionals in leading positions rate patient goals significantly higher than professionals that are not in leading positions (6.36 (6.28 to 6.44) vs 6.19 (6.15 to 6.22), p<0.01). Different employee goals need to be considered in decision-making processes to enhance employee motivation and the effectiveness of teamwork. DRKS00004589.
Keywords: 330